A terceira idade e a Internet: uma questão para o novo milênio - Dominguez Garcia, Heliéte [UNESP] (2001)
With the beginning of the new millennium, the Brazilian society is being transformed. It is believed that, by the year 2025, one in five Brazilian citizens will be 60 years old. The youngsters are prepared to deal with new technologies but the previous generations, which are currently considered to be the elderly, are not. In fact, they live in a society which is highly technological. Based on these facts, the purposes of this research are: to characterize the potential elderly user as for the use of the Internet in UNATI - UEL and SENAC - Londrina groups; to identify the use of the Internet by the elderly; to verify if the elderly are familiarized with the Internet and to detect their feelings and aspirations towards the Internet. The methodology used in this research was the case study under a qualitative-quantitative focus. A different questionnaire with open-ended and multiple choice questions was used for each institution studied in this research. The results obtained led us to the following conclusions: 1) both groups understand the importance of the use of the Internet nowadays; 2) it is easier and more comfortable for them to accomplish their daily tasks with the Internet; 3) the Internet brings information and stimulates creativity.